2016
DOI: 10.1136/heartjnl-2016-309585
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin treatment quality and prognosis in patients with mechanical heart valve prosthesis

Abstract: Objectives To study the impact of time in therapeutic range (TTR) and international normalised ratio (INR) variability on the risk of thromboembolic events, major bleeding complications and death after mechanical heart valve (MHV) implantation. Additionally, the importance of different target INR levels was elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 20 publications
3
26
4
3
Order By: Relevance
“…One possible explanation may be excessive dose elevation due to fear of thromboembolic complications in subtherapeutic INR levels, although the actual target INR is only slightly higher than that for AF patients. In fact, this finding is in line with the recent publication by Grzymala-Lubanski et al reporting a higher incidence of bleedings, death and total complications related to higher warfarin intensity in comparison to lower intensity of anticoagulation [14, 29]. …”
Section: Discussionsupporting
confidence: 89%
“…One possible explanation may be excessive dose elevation due to fear of thromboembolic complications in subtherapeutic INR levels, although the actual target INR is only slightly higher than that for AF patients. In fact, this finding is in line with the recent publication by Grzymala-Lubanski et al reporting a higher incidence of bleedings, death and total complications related to higher warfarin intensity in comparison to lower intensity of anticoagulation [14, 29]. …”
Section: Discussionsupporting
confidence: 89%
“…10 Overall, studies have shown that the risk of outcomes is higher in MMV patients compared with MAV patients. 11,22,24 We found that MMV patients had lower quality of VKA treatment compared with MAV patients, and because lower TTR is associated with higher risk of outcomes, MMV patients are, prima facie, at higher risk of outcomes compared with MAV patients.…”
Section: Discussionmentioning
confidence: 83%
“…Among patients with atrial fibrillation, studies have shown an association between low quality of VKA treatment and the risk of outcomes, whereas studies on patients with mechanical heart valve have shown contradictory results. [8][9][10][11] This nationwide, carefully designed study set out to examine the association between TTR and the risk of thromboembolic events and bleeding in patients with mechanical valve prostheses.…”
Section: Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…51 The low anticoagulant quality was correlated with the increase in risk of bleeding or thromboembolism. [52][53][54] Low TTR (<67%) was associated with the increase in D-dimer level. 55 Moreover, INR variation during the anticoagulation period (INR coefficient of variation, INR-CV%), which is another indicator of anticoagulation quality, was also a cause of the increase in D-dimer level.…”
Section: Use Of D-dimer To Evaluate Anticoagulation Qualitymentioning
confidence: 99%